2022
DOI: 10.1111/edt.12770
|View full text |Cite
|
Sign up to set email alerts
|

Medicolegal issues of peri‐anaesthetic dental injuries: A 21‐years review of liability lawsuits in France

Abstract: Background/Aim Peri‐anaesthetic dental injuries (PDI) represent a major source of potential malpractice claims against anesthesiologists. Studies about the medico‐legal aspects of PDI have mainly focused on liability insurance cases thus not encompassing those cases brought to court. The aim of this study was to assess the medico‐legal issues of PDI‐related liability lawsuits in France. Material and Methods A review of judicial decisions pertaining to PDI was conducted on a French legal database, spanning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…A recent comprehensive review of a French legal database identified just 24 lawsuits involving peri-operative dental injuries. 43 This relatively low case number highlights the rarity of these trials and reaffirms our assertation that the present review successfully captures all available court records on laryngoscope-mediated dental injuries. This report, therefore, may represent a valuable resource for predicting future litigation outcomes and may be referenced by expert witnesses under oath as precedent to justify verdicts.…”
Section: Discussionsupporting
confidence: 75%
“…A recent comprehensive review of a French legal database identified just 24 lawsuits involving peri-operative dental injuries. 43 This relatively low case number highlights the rarity of these trials and reaffirms our assertation that the present review successfully captures all available court records on laryngoscope-mediated dental injuries. This report, therefore, may represent a valuable resource for predicting future litigation outcomes and may be referenced by expert witnesses under oath as precedent to justify verdicts.…”
Section: Discussionsupporting
confidence: 75%
“…Although this is an event that occurs less than two in a hundred patients, according to most of the included studies, they are common complications of general anesthesia and account for a significant proportion of all medicolegal claims against anesthesiologists, especially in France, where they represent 40% of these claims [ 11 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are three major groups of causative factors: unfavorable patient anatomy, the experience and skill of the anesthesiologist who handles the airway, and the design of the laryngoscope blade [ 8 ]. In the study of Diakonoff et al, that review 21 years of law decisions, he found poor dentition in 15 of 19 cases, 78.9% preoperatively document, pre-existing periodontal disease in 16 cases (66.7%), and dental restorations or prostheses in seven cases (30.4%) [ 11 ]. Dental injury occurred in 21 cases (87.5%) where intubation was performed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations